Innovative therapeutic life story work : Developing trauma-informed practice for working with children, adolescents and young adults - Rose, Richard, 1933-; D. Gray, Deborah, ....- (Londen : Jessica Kingsley Publishers, 2017)
Dit boek verkent verschillende manieren om met levensverhalen te werken, een methode die getraumatiseerde kinderen helpt om vragen te stellen en problemen uit hun verleden op te lossen. Aan de hand van de ervaringen van mensen uit verschillende settings wordt een nuttig overzicht gegeven van de laatste ontwikkelingen op dit gebied.
This book explores different ways of carrying out life story work, a method which helps traumatized children question and resolve issues from their past. Using the experience of practitioners based in a range of settings, it provides a useful overview of the latest developments in the field.
Keywords: Therapeutisch, levensverhalen; Trauma